SYNCHRONIC AND DIACHRONIC APPROACHES TO THE STUDY OF LEXICAL UNITS (Modern education and development, 2025)
The article examines the synchronic and diachronic approaches to the study of lexical units in the English language. The synchronic approach analyzes vocabulary at a specific stage of its existence, focusing on meaning, structure, and usage. In contrast, the diachronic approach studies changes and the historical development of lexical units over time. Special attention is given to the advantages and limitations of each approach and their role in the comprehensive analysis of the lexical system. Examples illustrate shifts in the meaning and form of words, emphasizing the dynamic nature of language. The paper concludes that both approaches are essential in lexicography, semantics, and historical linguistics.